2020
DOI: 10.1002/1878-0261.12624
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalized cytoplasmic p27 activates PAK1‐mediated metastasis and is a prognostic factor in osteosarcoma

Abstract: The development of pulmonary metastasis is the leading cause of death in osteosarcoma (OS), which is the most common malignant bone tumor in children. We have previously reported that the tumor suppressor p27 (KIP1, CDKN1B) is frequently mislocalized to the cytoplasm of OS. However, its prognostic significance and metastatic mechanism are still elusive. Here, we show that cytoplasmic p27 significantly correlated with a higher metastatic status and poorer survival of OS patients (n = 136, P < 0.05), highlightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Recently, an increasing number of diagnostic and prognostic biomarkers of osteosarcoma patients have been identified. For example, Chen et al [ 5 ] reported that tumor suppressor p27 is a novel biomarker for the metastasis and survival status in osteosarcoma patients. Moreover, Huang et al [ 6 ] discovered that dysregulated circRNAs serve as prognostic and diagnostic biomarkers in osteosarcoma patients, and the relative potential mechanism mainly attributes to the regulation of downstream signaling pathways by sponging microRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of diagnostic and prognostic biomarkers of osteosarcoma patients have been identified. For example, Chen et al [ 5 ] reported that tumor suppressor p27 is a novel biomarker for the metastasis and survival status in osteosarcoma patients. Moreover, Huang et al [ 6 ] discovered that dysregulated circRNAs serve as prognostic and diagnostic biomarkers in osteosarcoma patients, and the relative potential mechanism mainly attributes to the regulation of downstream signaling pathways by sponging microRNA.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that the LINC00662/miR-30b-3p/ELK1 axis may be involved in the progression of osteosarcoma by regulating these signalling pathways. In addition, some potential downstream genes of miR-30b-3p, such as ATG5 [61], PAK1 [62], FOXP4 [63], and MYO10 [64] also exerted crucial roles in osteosarcoma. We speculated that these genes may be also involved in the regulatory mechanism of LINC00662/miR-30b-3p in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, soft tissue deficiency after segmental mandibular resection was small because of the exophilic nature of the tumor. The presence of mislocalized cytoplasmic p27 is reported to be associated with higher metastatic status and poorer survival of osteosarcoma [17]. As clinical factors, proximal location of osteosarcoma in the long bone of an extremity portends a worse clinical outcome than tumors located in the distal long bones [18].…”
Section: Discussionmentioning
confidence: 99%